Evidence of antimicrobial resistance (AMR) in food crop value chains - CGIAR Research Program on Agriculture for Nutrition and Health (2021)
A report was published on LSHTM Research Online in 2021. The entry has been updated with the link to the 2022 peer-reviewed publication. Several international AMR initiatives such as those led by the United Nations Environment Programme (UNEP) and the AMR Coalition have asked to use the findings.